IMPLEMENTASI PEMUPUKAN TANAMAN KELAPA SAWIT (Elaeis guineensis Jacq) POLA PERKEBUNAN KKPA PADA LAHAN GAMBUT DI KABUPATEN ROKAN HILIR DAN KABUPATEN SIAK - Edi Karsino; Islan ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
Goverment formed KKPA plantation system to develop palm oil plant in Indonesia, however lack of availability fertile land conduce peatlans as alternative to use as growth media palm oil plant. Peatland has some weakness, that are low soil pH and nutrient, therefore it is required nutrient supply as fertilizer. Implementation of fertilization should pay attention to 5 factors: right kind, dose, frequency, quality and fertilization techniques. This research aims to know implementation of fertilization, cultivation techniques and productivity of palm oil plant KKPA plantation system on peatlands in Rokan Hilir and Siak regency. This research use survey method and determination population in Stratified Random Sampling and number sample of farmer respondents 10% from populations. Variable of observation are seedlings, land preparation, cultivation, palm oil plant maintenance, fertilization and harvesting. The result show that KKPA farmer in Rokan Hilir regency only 39,27% which following fertilization concept while in Siak regency 63,29%. Harvest farmer in Rokan Hilir regency as much as 747,6 kg/ha/month which harvest result in Siak regency as much as 1.126,7 kg/ha/month. Keywords: Palm oil, KKPA and Fertilization.